CSF apolipoprotein B is associated with early tau pathology and selective activation of a cytokine cascade in cognitively unaffected subjects with a parental history of Alzheimer's disease. (31st December 2021) - Labonte, Anne; Picard, Cynthia; Nilsson, Nathalie I.V.; Rosa‐Neto, Pedro; Breitner, John; Villeneuve, Sylvia; Poirier, Judes; ,
Abstract: Background: We examine the role of CSF apolipoprotein B (apoB) as a putative indicator of early tau pathology in pre‐symptomatic Alzheimer's disease (AD). Method: Among 129 cognitively unimpaired elderly at increased risk of AD (PREVENT‐AD cohort), we assessed blood and cerebrospinal fluid apoB, apoC3 and apoE protein levels using the the Milliplex APOMAG‐62k human apolipoprotein cardiovascular disease multiplex kit (EMD‐Millipore, MA, USA) with those of amyloid β42, total tau and phosphorylated tau (the Innotest enzyme‐linked immunosorbent assay kit (Fujirebio, Ghent, Belgium). We contrasted results with alterations in several inflammation biomarkers using Luminex's Milliplex HCYTMAG60PMX29BK xMap technology ((EMD‐Millipore, USA). Result: Among cognitively unimpaired participants, we observed significant correlations between baseline CSF, but not blood, apoB levels and both CSF t‐ tau (R 2 = 0.23, P < 0.0001) and P‐ tau (R 2 = 0.28, P < 0.0001). No association was detected between CSF apoB and CSF Aβ42 levels. Using multiple brain blood barrier permeability assays, we found that the contribution from peripheral apoB to be negligible. Concomitant analyses of several key cytokines and chemokines in the CSF failed to show any association following FDR correction, except for IL‐15 (R 2 : 0.38, p < 0.001). IL‐15, a potent inducer of reactive gliosis in both astrocytes and microglia, is normally synthesized by compromised neurons in the CNS. Conclusion: CSF apoB, which is normally produced by microglia, markedly associates with early tau dysregulation and the activation of select cytokines in asymptomatic subjects, years before the onset of symptoms.